Study of the effects of freezing process on nutritional value of 17 fish species marketed in São Paulo State, Brazil - Tomita, Rúbia Yuri; Carvalho, Síbilla dos Santos (Revista do Instituto Adolfo Lutz, 2021)
Freezing is an important strategy to keep fish quality and make the species available the whole year. Its effects on the nutritional value of 17 fish species were studied in samples of entire fish, fillets or pieces. One portion of homogenized flesh was analyzed just after purchase (fresh sample). The other portion was packed in polyethylene bag, sealed, quick frozen (-80°C), stored properly at -18°C and analyzed after 12 months (frozen sample). Moisture, ash and protein content were tested using Brazilian Supply, Livestock and Agriculture Ministry methodologies. Lipid content was analyzed through Bligh and Dyer method. Carbohydrate content and caloric value were calculated, using NIFEXT fraction and Atwater coefficient, respectively. When fresh and frozen samples were compared, moisture and ash content showed significant difference (p<0.05) for 17.65% and 11.77% species, respectively. Lipid and protein contents were the most affected parameters, as they were altered in 29.40% of the studied species (p<0.05), and therefore, highlighted the importance of the conservation technology used on nutritional quality of fishery products. Mullet (M. brasiliensis) and Atlantic salmon (S. salar) had their nutritional composition more affected by freezing process with five and four altered parameters, respectively, from the six studied.